The reality of e-learning and the obstacles to using it in university education from the viewpoint of the students of the College of Imam Al-A’dham in Iraq: واقع التعليم الإلكتروني ومعوقات استخدامه في التعليم الجامعي من وجهة نظر طلبة كلية الإمام الأعظم (رحمه الله) الجامعة بالعراق - Nazar Salih Abdulhussein, Aseel Shakir Ibrahim (Journal of engineering sciences and information technology, 2020)
This research aims to reveal the reality of e-learning and the obstacles to use it in university education under Corona pandemic situation from the viewpoint of the students of Al-Imam Al- Adham College University in Iraq. The study sample involved 462 students (males and females) from the college’s departments of all levels, in addition, 31 staff members from the scientific departments of the college. An electronic questionnaire was applied, consisting of 30 paragraphs, of which (22) were related to the reality of using e-learning and its obstacles to utilize it. Thus, 8 paragraphs related to the infrastructure of the college, and the study was applied in the second semester of the academic year (2019/2020). The results also revealed the most important obstacles of using e-learning in the college with arithmetic average were 3.46 and percentage (69.3%). This is including the large percentage of students feel that their future is ambiguous under the current circumstances, with an average of 4.28, and a percentage 85.6%. Followed by, there is a barrier between the student and teacher, with an arithmetic average 3.90 and percentage 84%. The results also revealed the weakness of the infrastructure in the college’s departments, as there are only 17 computer labs available for 32 scientific departments within the college. In addition, there are available only 157 computers in 13 laboratories, which is even not consistent with the number of technicians in the laboratories. The results also indicated the lack of display devices and maintenance units in the faculty laboratories and the lack of internet service in the most faculties of the department laboratories. Finally, the study presented some recommendations and suggestions regarding this issue.